Assessment of Techniques for Contact-Pair Detection in Solid Mechanics - Quaranta, F.; Alves, J. L. D. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1998)
This work presents some basic concepts of a technique used for modeling contact-impact problems between deformable solids through penalized finite element formulation handling the impenetrability condition and conserving momentum. This technique uses the concept of discrete particles and provides a way to treat general contact configurations due an automatic search for the elements involved in the phenomenon. An efficiency analysis of different algorithms used in this search is also presented. The algorithms studied were used in a finite element code, developed at PEC/COPPE, for explicit transient analysis of the non-linear behavior of axyssimetric solids.